On Relativized Minimality, Memory and cue-based parsing - Ortega Santos, Ivan (IBERIA: An International Journal of Theoretical Linguistics, 2011)
It is argued that Relativized Minimality (RM, Rizzi 1990 and Starke 2001, a.o.) is grammaticized as a real constraint that is functionally grounded as a response to memory. In particular, it is shown that a cue-based retrieval parser (Van Dyke &Lewis 2003, Lewis & Vasishth 2005), according to which the integration of incoming words into existing interpretation is limited by retrieval interference and decay, can explain a number of features of RM. This analysis can capture both the properties that RM and general cognitive phenomena share (e.g., the similarity-based interference) and the features which are unique to this constraint, (e.g., the role of c-command). Recent developments in research on aphasia (Grillo 2008) and language acquisition (Adani et al. 2010) support this interpretation. Furthermore, the issue of crosslinguistic variation and a number of arguments against coding islands in the grammar (e.g., Kluender 2004 and Hofmeister & Sag2010) are addressed.